Structural Barriers of Shariah Life Insurance for Gig Economy Workers (Takaful Design) - Ardy Firman Syah (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2025)
This study aims to examine the structural life insurance protection gap experienced by gig workers and to assess the potential of Shariah-compliant life insurance (family takaful) as an inclusive risk protection mechanism. The central research question asks how gig economy labor characteristics interact with existing takaful design assumptions to produce institutional exclusion from life insurance coverage. Employing a qualitative research design, the study draws on semi-structured interviews with gig workers, takaful practitioners, Shariah scholars, and regulators, complemented by document analysis of takaful contracts, regulatory guidelines, and fatwas. Thematic analysis is used to identify patterns of misalignment between gig workers’ income realities and insurance structures. The findings reveal that low participation in life insurance among gig workers is not driven by lack of risk awareness or religious resistance, but by structural incompatibility. Fixed contributions, long-term contractual assumptions, and formal employment bias systematically exclude workers with irregular, platform-mediated incomes. Shariah principles such as ta’awun and tabarru’ are found to be normatively inclusive but weakly operationalized in current takaful practice. The study suggests that gig-adaptive takaful models—featuring flexible contributions, risk-focused coverage, and platform-facilitated enrollment—are necessary to translate Shariah principles into effective life-cycle protection for gig workers.